High Miscibility Compatible with Ordered Molecular Packing Enables an Excellent Efficiency of 16.2% in All‐Small‐Molecule Organic Solar Cells. Issue 5 (13th December 2021) - Zhang, Lili; Zhu, Xiangwei; Deng, Dan; Wang, Zhen; Zhang, Ziqi; Li, Yi; Zhang, Jianqi; Lv, Kun; Liu, Lixuan; Zhang, Xuning; Zhou, Huiqiong; Ade, Harald; et al.
Abstract: In all‐small‐molecule organic solar cells (ASM‐OSCs), a high short‐circuit current ( J sc ) usually needs a small phase separation, while a high fill factor (FF) is generally realized in a highly ordered packing system. However, small domain and ordered packing always conflicted each other in ASM‐OSCs, leading to a mutually restricted J sc and FF. In this study, alleviation of the previous dilemma by the strategy of obtaining simultaneous good miscibility and ordered packing through modulating homo‐ and heteromolecular interactions is proposed. By moving the alkyl‐thiolation side chains from the para ‐ to the meta ‐position in the small‐molecule donor, the surface tension and molecular planarity are synchronously enhanced, resulting in compatible properties of good miscibility with acceptor BTP‐eC9 and strong self‐assembly ability. As a result, an optimized morphology with multi‐length‐scale domains and highly ordered packing is realized. The device exhibits a long carrier lifetime (39.8 μs) and fast charge collection (15.5 ns). A record efficiency of 16.2% with a high FF of 75.6% and a J sc of 25.4 mA cm −2 in the ASM‐OSCs is obtained. These results demonstrate that the strategy of simultaneously obtaining good miscibility with high crystallinity could be an efficient photovoltaic material design principle for high‐performance ASM‐OSCs. Abstract : Two novel small‐molecule donors with thioalkyl chains in the para ‐ (P‐PhS) and the meta ‐position (M‐PhS) are synthesized to regulate surface tension and molecular packing. An optimized morphology with small domains and ordered packing is simultanously obtained in the M‐PhS:BTP‐eC9 blend, promoting a record power conversion efficiency (PCE) of 16.2% with excellent ( FF  × J sc ) in all‐small‐molecule organic solar cells (ASM‐OSCs).